First-Principles Study of Electronic Properties and Robust Half Metallicity of Mixed Sr1-xCaxBeO3 (x = 0.25) Perovskite: Investigation of Electronic Properties and Half Metallicity in Sr1-xCaxBeO3 Perovskite (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The electronic and magnetic properties of pristine and Ca-doped SrBeO3 have been investigated using full potential linearized augmented plane wave (FPLAPW) method based on density functional theory (DFT). The generalized gradient approximation (GGA) has been used to treat exchange and correlation potentials. Our results reveal that pristine SrBeO3 and mixed Sr1-xCaxBeO3 (x = 0.25) perovskites have 100 spin polarization at Fermi level which ensure the robust half metallicity even after Ca-doping in SrBeO3 perovskite. The magnetic moment of ~ 2.0 μB has been obtained for both which is consequence of hybridization of alkaline earth metals (Ca and Sr) p-states and O-p states. Due to the robust half metallicity and significant magnetism, the mixed Sr1-xCaxBeO3 (x = 0.25) perovskite may also be useful in spintronic devices.